2015
DOI: 10.1017/s0007485315000206
|View full text |Cite
|
Sign up to set email alerts
|

Response to conspecific and heterospecific semiochemicals by Sesamia nonagrioides (L.) (Lepidoptera: Noctuidae) gravid females

Abstract: The Mediterranean corn borer, Sesamia nonagrioides, occurs sympatrically in the northeast of Spain with other lepidopteran pests such as Ostrinia nubilalis and Mythimna unipuncta. In this study, we evaluated the electrophysiological and behavioural response of mated and unmated females and males of S. nonagrioides to their own complete pheromone blend, to its own four components separately, and to the pheromone components of the sympatric species O. nubilalis and M. unipuncta. Results of the electroantennogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The detection of conspecific pheromone, or particular compounds therein, may also influence female foraging and oviposition, and the resulting behavioral changes could impact levels of both intra-and interspecific competition. Cruz & Eizaguirre (2015) demonstrated that the antennae of females, as those of males, of the Mediterranean corn borer, Sesamia nonagrioides (L.), respond to both the full blend and the individual components of the sex pheromone, but the response levels differed significantly between the sexes. Furthermore, they found that EAG responses differed between mated and unmated females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of conspecific pheromone, or particular compounds therein, may also influence female foraging and oviposition, and the resulting behavioral changes could impact levels of both intra-and interspecific competition. Cruz & Eizaguirre (2015) demonstrated that the antennae of females, as those of males, of the Mediterranean corn borer, Sesamia nonagrioides (L.), respond to both the full blend and the individual components of the sex pheromone, but the response levels differed significantly between the sexes. Furthermore, they found that EAG responses differed between mated and unmated females.…”
Section: Discussionmentioning
confidence: 99%
“…The diel periodicity of female calling is influenced by a wide range of both abiotic and biotic factors, such as temperature, photoperiod, wind speed, humidity, host plants, and female age (McNeil, ). However, changes in female calling behavior in response to conspecific pheromones, referred to as pheromone autodetection (Ochieng et al., ), has received considerably less attention than other parameters, even though the phenomenon has been reported in Arctiidae (Schneider et al., ; Grant & O'Connell, ), Tortricidae (den Otter et al., , ; Palaniswamy & Seabrook, ; De Cristofaro et al., ; DeLury et al., ; Stelinski et al., ; Gökçe et al., ; Harari et al., ), Sphingidae (Kalinová et al., ), Sesiidae (Pearson & Schal, ), and Noctuidae (Light & Birch, ; Ljungberg et al., ; Fan et al., ; Groot et al., ; Silvegren et al., ; Yang et al., ; Cruz & Eizaguirre, ). As seen from these studies, the behaviors expressed when exposed to conspecific pheromones, and the potential benefits accrued from such changes, vary considerably among species.…”
Section: Introductionmentioning
confidence: 99%
“…These contradictory results from separate studies with G. molesta highlight variation of behavioral responses depending possibly on assay conditions. Three tortricids ( Eupoecilia ambiguella (Hübner), Pandemis pyrusana (Kearfott), and Lobesia botrana (Denis and Schiffermüller)) and an arctiid ( Euplagia quadripunctaria (Poda)) displayed no observable behavioral responses when exposed to pheromone (Refs [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] in Table 1 ).…”
Section: Types Of Evidencementioning
confidence: 99%
“…So far only one lepidopteran species has verified attraction to conspecific pheromone in the lab. Gravid females of the noctuid moth, Sesamia nonagrioides (Lefebvre), were attracted to pheromone sources in dual-choice olfactometer assays [ 36 ].…”
Section: Types Of Evidencementioning
confidence: 99%
“…the ability to detect same sex pheromone) is common among insect signallers that emit long-range sex pheromones, including a number of moth species 26 , and may have evolved to adjust calling behaviour, or the calling site, to the presence of conspecific signallers 27 . Also, female attraction to female pheromone has been described in trapping 28 30 and laboratory experiments 31 , and there is one report of a lab bioassay where multiple females line up about 20 cm downwind of each other while calling 32 . Pheromonal chorusing has been reported in both Lepidoptera 27 and Coleoptera 33 and, as was observed in frogs 34 and crickets 35 , the coleopteran pheromonal chorus contained non-signalling “satellite females” 36 .…”
Section: Introductionmentioning
confidence: 99%